Molecular dynamics of the DNA-binding domain of the papillomavirus E2 transcriptional regulator uncover differential properties for DNA target accommodation - Falconi, M. (2007)
Papillomaviruses are small DNA tumor viruses that infect mammalian hosts, with consequences from benign to cancerous lesions. The Early protein 2 is the master regulator for the virus life cycle, participating in gene transcription, DNA replication, and viral episome migration. All of these functions rely on primary target recognition by its dimeric DNA-binding domain. In this work, we performed molecular dynamics simulations in order to gain insights into the structural dynamics of the DNA-binding domains of two prototypic strains, human papillomavirus strain 16 and the bovine papillomavirus strain 1. The simulations underline different dynamic features in the two proteins. The human papillomavirus strain 16 domain displays a higher flexibility of the β2-β3 connecting loop in comparison with the bovine papillomavirus strain 1 domain, with a consequent effect on the DNA-binding helices, and thus on the modulation of DNA recognition. A compact β-barrel is found in human papillomavirus strain 16, whereas the bovine papillomavirus strain 1 protein is characterized by a loose β-barrel with a large number of cavities filled by water, which provides great flexibility. The rigidity of the human papillomavirus strain 16 β-barrel prevents protein deformation, and, as a consequence, deformable spacers are the preferred targets in complex formation. In contrast, in bovine papillomavirus strain 1, a more deformable β-barrel confers greater adaptability to the protein, allowing the binding of less flexible DNA regions. The flexibility data are confirmed by the experimental NMR S2 values, which are reproduced well by calculation. This feature may provide the protein with an ability to discriminate between spacer sequences. Clearly, the deformability required for the formation of the Early protein 2 C-terminal DNA-binding domain-DNA complexes of various types is based not only on the rigidity of the base sequences in the DNA spacers, but also on the intrinsic deformability properties of each domain. © 2007 The Authors.